Evaluation of a human BCG challenge model to assess antimycobacterial immunity induced by BCG and a candidate TB vaccine, MVA85A, alone and in combination - Harris, S; Meyer, J; Satti, I; Marsay, L; Poulton, I; Tanner, R; Minassian, A; Fletcher, H; McShane, H (Oxford University Press, 2013)
Background. A new vaccine is urgently needed to combat tuberculosis. However, without a correlate of protection, selection of the vaccines to take forward into large-scale efficacy trials is difficult. Use of bacille Calmette-Guérin (BCG) as a surrogate for human Mycobacterium tuberculosis challenge is a novel model that could aid selection. Methods. Healthy adults were assigned to groups A and B (BCG-naive) or groups C and D (BCG-vaccinated). Groups B and D received candidate tuberculosis vaccine MVA85A. Participants were challenged with intradermal BCG 4 weeks after those who received MVA85A. Skin biopsies of the challenge site were taken 2 weeks post challenge and BCG load quantified by culture and quantitative polymerase chain reaction (qPCR). Results. Volunteers with a history of BCG showed some degree of protective immunity to challenge, having lower BCG loads compared with volunteers without prior BCG, regardless of MVA85A status. There was a significant inverse correlation between antimycobacterial immunity at peak response after MVA85A and BCG load detected by qPCR. Conclusion. Our results support previous findings that this BCG challenge model is able to detect differences in antimycobacterial immunity induced by vaccination and could aid in the selection of candidate tuberculosis vaccines for field efficacy testing.